2022
DOI: 10.7759/cureus.25200
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Transorbital Ultrasonographic Measurement of Optic Nerve Sheath Diameter (ONSD) for Estimation of Intracranial Pressure Following Cerebrospinal Fluid Diversion Surgery

Abstract: Background and aim Raised intracranial pressure (ICP) can be estimated by various invasive as well as non-invasive techniques. Optic nerve sheath diameter (ONSD ) is a bedside non-invasive technique for assessment of ICP as a regular follow-up tool and has added advantage over CT scan/MRI, which require patient transfer to the suite. Cerebrospinal fluid (CSF) diversion procedures such as a ventriculoperitoneal shunt or external ventricular drainage are commonly done to relieve symptoms of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…An experimental study revealing that ONSD decreases with lumbar puncture also demonstrated the ability to collect real-time ONSD measurements [ 218 ]. Similar results were shown by studies before and after ventriculo-peritoneal shunt surgery [ 219 ] and during surgery [ 220 ].…”
Section: Approaches Of Non-invasive Measurementssupporting
confidence: 89%
“…An experimental study revealing that ONSD decreases with lumbar puncture also demonstrated the ability to collect real-time ONSD measurements [ 218 ]. Similar results were shown by studies before and after ventriculo-peritoneal shunt surgery [ 219 ] and during surgery [ 220 ].…”
Section: Approaches Of Non-invasive Measurementssupporting
confidence: 89%
“…The authors also found that an ONSD cutoff value of 5.85 mm was able to predict ICP > 20 mm Hg with a sensitivity of 92.3% and a specificity of 85.7%. 4 In a recently published prospective study conducted by Sahu et al on 30 adults scheduled for surgical procedures for the management of intracranial hypertension, the authors observed that an ONSD cutoff value > 5.5 mm predicted ICP > 20 mm Hg with a sensitivity of 100% and a specificity of 75%. The authors also identified ONSD cutoffs of 6.3, 6.5, and 6.7 mm for predicting ICP greater than 25, 30, and 35 mm Hg, respectively.…”
Section: Onsd Measurementsmentioning
confidence: 98%
“…CSF diversion procedures such as ventriculoperitoneal (VP) shunt surgery, endoscopic third ventriculostomy (ETV), or placement of an external ventricular drain are frequently performed to relieve raised ICP in patients with hydrocephalus. 4 While invasive methods continue to remain the proverbial "gold standard" for monitoring ICP, they are associated with several complications such as infection, hemorrhage, and device failure or disconnection. 5 In addition, invasive ICP monitoring is relatively contraindicated in the presence of coagulopathy, which is commonly encountered in patients with traumatic brain injury.…”
Section: Introductionmentioning
confidence: 99%